Reduced vancomycin susceptibility in porcine ST9 MRSA isolates - Kwok, Gabriella M.; O'Donoghue, Margaret M.; Doddangoudar, Vijaya C.; Ho, Jeff; Boost, Maureen V. (Frontiers in Microbiology, 2013)
Porcine strains of livestock-associated methicillin resistant Staphylococcus aureus (LA-MRSA) have been recognized in many countries and have been shown to be able to cause human infection. Resistance to non-beta lactam antibiotics has been reported but non-susceptibility to vancomycin, which is known to occur in human MRSA, has so far not been observed in LA-MRSA. Such resistance is typically fairly low level involving changes in the cell wall thickness. The development of resistance is usually preceded by presence of a sub-population having an increased MIC, which is selected for by exposure to vancomycin. This study investigated vancomycin susceptibility of one hundred porcine MRSA isolates using three MIC methods including spiral gradient endpoint (SGE) technique which allows visualization of more resistant sub-populations. SGE revealed 16 strains with an MIC above 2.0 mg/L, of which 14 were determined to have MIC 4 mg/L by agar dilution. SGE revealed a further two isolates with MIC 2 mg/L. In addition, trailing endpoints not reaching resistance were present in 26 isolates with MIC 1.5 mg/L, the presence of vancomycin non-susceptibility in porcine isolates is of concern and further monitoring of LA-MRSA is essential.